THE RETICENCE OF STBA PONTIANAK STUDENTS IN LEARNING ENGLISH - Arungtuanggi Limbong, Darajah Hani (LPPM STBA Pontianak, 2020)
The present study reported on the reticent factors and its behaviours demonstrated by the third-semester students of the academic year 2019/2020 in STBA Pontianak. They were all 2A1 class with 38 students majoring in English literature. Ten students were selected to be asked in interview. The study applied a qualitatively descriptive method which data were obtained from direct observationand semi-structured interview, then, being analysed in three steps. The research finding indicated that the students were reluctant to speak and remained reticent in language classroom due to three aspects, namely students factors as the most various influential factors, lecturer factors, and cultural factors. Moreover, speaking more in their native language, avoiding communication, sitting at the back and in the middle, being passive, unwilling to initiate interaction, giving a short response, relying on memorization, doing less interaction, and needing more a waited-time, were identified as reticent behaviours.